Role of Bariatric Surgery for Reducing Glycated Hemoglobin (Hba1c) in Type 2 Diabetes Mellitus Compared to Current Medicaments Therapy - Firas Farisi Alkaff; Ricardo Adrian Nugraha; Michael Jonatan; Sulistia wati (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Type II is the most common type of Diabetes Mellitus, and one of the most common non-communicable diseases globally. In Indonesia, diabetes contributes to 6% of total deaths. Current medicaments therapy available can only control the disease, not to cure it. Recently, there has been new treatment that has been recommended into standard care for type II Diabetes Mellitus. It was in September 2015 at the second Diabetes Surgery Summit that the introduction of bariatric surgery has been put into standard care for type II Diabetes Mellitus.Objective: To draw a comparison of the effectiveness between bariatric surgery and current medicaments therapy in reducing HbA1c to achieve remission.Methods: Literature study was conducted to identify relevant literature showing comparison study between bariatric surgery and medicaments therapy, and comparison study between types of bariatric surgery. 16 Studies are included in this article from 230 studies found.Results: HbA1c remission in bariatric surgery is significantly higher than medicaments therapy in all studies, ranging from 66.7% vs 0% to 57.1% vs 9.5% during 6-24 months after therapy. Between all types of bariatric surgery, most of the studies shows that Roux-en-Y Gastric Bypass achieves HbA1c remission higher than other types of surgery.Conclusion: Bariatric surgery is better than current medicaments therapy in achieving HbA1c remission.